Analisis Nilai-Nilai Sastra dan Bentuk Nasionalisme dalam Lagu Yaa Lal Wathon Ciptaan KH. Abdul Wahab Hasbullah - Yuniar Mujiwati; Ana Ahsana El-Sulukiyyah (Jurnal Educazione : Jurnal Pendidikan, Pembelajaran dan Bimbingan dan konseling, 2017)
On Augusts, Indonesian people always celebrate the Indonesian Independence Day. Every people in Indonesia feel the nationalism including the santri (Moslem students). Yaa Lal Wathon song added in the flag ceremony of Independence Day celebration is one of the ways to increase our nationalism. This research aims to analyze the lyrics of Yaa Lal Wathon song, to analyze the literature values and nationalism classification. The method of this research is descriptive study focusing on the content analysis. The result is the lyrics of this song, beginning from the first sentence to the last sentence, the literature values found are aesthetic values, philosophical values, and religious values. The classifications of nationalism are also found like romantic nationalism, nationality nationalism, and nation nationalism. This song is chosen to develop and increase the early nationalism values for our next generation as the purpose of the composer, KH. Abdul Wahab Hasbullah, one of our national heroes.Keywords: Literature Values, Nasionalism Characters, Yaa Lal Wathon, KH. Abdul Wahab Hasbullah